Antusiasme untuk Menjadi Siswa di Sekolah Dasar - Muhammad Rizki; Hidar Amaruddin (Jurnal Pendidikan Indonesia, 2026)
Students' enthusiasm and passion for participating in school learning activities are declining. This is evident in low student participation in learning activities, minimal motivation to achieve, and limited involvement in extracurricular activities. However, the principal plays a strategic role as an educational leader capable of creating a positive, inspiring, and enjoyable school climate for students. This study focuses on the problem of the low number of new students enrolling in schools each year. This study aims to formulate a conceptual model of the causes of low interest among new students in the context of school education. This study uses a qualitative case study approach. Data collection techniques include interviews, observation, and documentation. The data sources used are one principal, 4 class teachers, and one village head. The data analysis technique used is based on Miles & Huberman, which includes data collection, data reduction, data presentation, and conclusion drawing, as well as testing the data's validity through source and technical triangulation. The results of the study indicate that the principal is a central figure and a strong foundation for establishing and running active communication and collaboration within the school system. The implications of this study indicate that the principal is essential to developing effective policies and plans to maintain school stability.